Use of Noncontrast Computed Tomography of the Inferior Vena Cava for Real-Time Imaging Guidance for the Placement of Inferior Vena Cava Filters - Winkler, Michael A.; Majmudar, Palak M.; Landwehr, Kevin P.; Hobbs, Stephen B.; Saha, Sibu P. (International Journal of Angiology, 2015)
Appropriate placement of an inferior vena cava (IVC) filter necessitates imaging of the renal veins because when an IVC filter is deployed its tip should be at or below the inferior aspect of the inferiormost renal vein. Traditionally, imaging during placement of IVC filters has been with conventional cavography and fluoroscopy. Recently, intravascular ultrasound has been used for the same purpose but with additional expense. Morbidly obese patients often exceed the weight limit of fluoroscopy tables. In addition, short obese patients are at risk of falling from narrow fluoroscopy tables. For such patients, computed tomography (CT) guidance is a viable alternative to conventional fluoroscopic guidance.IVC placement was performed in the CT suite for two obese patients who exceeded the weight limits of the available fluoroscopy tables. In one case, a Vena-Tech filter (Braun Medical, Melsungen, Germany) was placed using CT fluoroscopy. In the second case, a Recovery (Bard, Murray Hill, NJ) filter was placed using intermittent limited z-axis scanning.In the first case, the filter was placed below the level of the renal veins and above the confluence of the iliac veins, which is acceptable placement. In the second case, with refinement of technique, the filter tip was placed less than 1 cm below the inferiormost renal vein, which is considered optimal placement.CT of the IVC precisely images the renal veins and can characterize their number and their confluence with the IVC. CT guidance is a viable alternative to fluoroscopic guidance for the placement of IVC filters in morbidly obese patients.
Keywords: inferior vena cava; computed tomography; filterplacementguidance; deep vein thrombosis; obesity